Answer:
y = (3/32)(x^2 - x - 30)
Explanation:
The equation of this parabola looks like y = (x - 6)(x + 5).
It is possible that there's a constant coefficient: y = a(x - 6)(x + 5).
Multiplying out y = (x - 6)(x + 5), we get y = x^2 - x - 30.
Does (-1, 3) satisfy this equation? 3 = (-1)^2 - (-1) - 30 NO, this is not true.
So, use the equation y = a(x - 6)(x + 5) instead.
This is equivalent to y = a(x^2 - x - 30). Determine the value of a that makes this equation true for the point (-1, 3):
3 = a[(-1)^2 + 1 + 30], or
3 = a[32]. Thus, a must be 3/32, and the equation is
y = (3/32)(x^2 - x - 30)
If possible answer choices are given to you, please share them. Thanks